The Molecular Pathology of Eye Tumors: A 2019 Update Main Interests for Routine Clinical Practice - Nahon-Esteve, Sacha; Martel, Arnaud; Maschi, Célia; Caujolle, Jean-Pierre; Baillif, Stéphanie; Lassalle, Sandra; Hofman, Paul (Current Molecular Medicine, 2019)
Over the last few years, we have seen constant development of molecular pathology for the care of patients with cancer. The information obtained from molecular data has transformed our thinking about the biological diversity of cancers, particularly in the field of ophthalmic oncology. It has reoriented the way in which therapeutic decisions and decisions concerning patient surveillance are made, both in the area of pediatric cancers, including rhabdomyosarcoma and retinoblastoma, and adult cancers, such as uveal melanoma and lymphomas. A better definition of the molecular classification of these cancers and of the different biological pathways involved is essential to the understanding of both the pathologist and the onco-ophthalmologist. Molecular tests based on targeted or expanded analysis of gene panels are now available. These tests can be performed with tumor tissue or biofluids (especially blood) to predict the prognosis of tumors and, above all, the benefit of targeted therapies, immunotherapy or even chemotherapy. Looking for the BAP1 mutation in uveal melanoma is essential because of the associated metastatic risk. When treating retinoblastoma, it is mandatory to assess the heritable status of RB1. Conjunctival melanoma requires investigation into the BRAF mutation in the case of a locally advanced tumor. The understanding of genomic alterations, the results of molecular tests and/or other biological tests predictive of a therapeutic response, but also of the limits of these tests with respect to the available biological resources, represents a major challenge for optimal patient management in ophthalmic oncology. In this review, we present the current state of knowledge concerning the different molecular alterations and therapeutic targets of interest in ophthalmic oncology.
Keywords: eye tumors